Implementation of the Ziegler-Nichols Proportional Integral Derivative (PID) Method on Coffee Bean Roasting Machine Controls - Nggala, Liberius Harsen; Nachrowie; Subairi (Universitas Panca Marga, 2023)
PID control has been used in simple or complex machine control. Coffee is an agricultural commodity that is widely used as a food and beverage ingredient. Coffee bean roasting is required before it can be further processed (consumed). This research was conducted to create an automatically controlled coffee bean roaster using the Ziegler-Nichols type-1 PID method. This coffee bean roaster is made with a series of roasters, DC motors, servo motors, ESP32, thermocouple sensors, load cell sensors, ceramic stoves, and other supporting components. The bitterness variations of the coffee beans produced are